A measles outbreak in Kansai International Airport, Japan, 2016: Analysis of the quantitative difference and infectivity of measles virus between patients who are immunologically naive versus those with secondary vaccine failure. Issue 6 (29th December 2020) - Kurata, Takako; Yamamoto, Seiji P.; Nishimura, Hiroshi; Yumisashi, Takahiro; Motomura, Kazushi; Kinoshita, Masaru
Abstract: Since the elimination of the measles virus, patients with vaccination records for the measles‐containing vaccine have increased in Japan. According to several studies, the transmission risk from previously immunized patients, especially those with secondary vaccine failure (SVF), is lower than that from those with primary measles infections. Immunological features of SVF were identified per specific immunoglobulin G (IgG) induction with high avidity and high plaque reduction neutralization antibody concentration. However, the virological features of SVF have not been well investigated. To examine not only immunological but also virological differences between SVF and immunologically naive patients, throat swabs and blood and urine specimens of 25 patients with confirmed measles infection after an outbreak at the Kansai International Airport in 2016 were analyzed. Patients were categorized as naive ( n = 3) or with SVF ( n = 22) based on measles‐specific IgG antibody concentrations and their avidity. Virus isolation and quantitative real‐time polymerase chain reaction were performed to quantify the viral load in clinical specimens and estimate the infectivity in each specimen. The number of viral genome copies in the blood specimens of those with SVF was significantly different and approximately 1 out of 100 of that in immunologically naive patients. However, genome copy numbers in throat swabs and urine specimens were not significantly different between the groups. The virus was isolated only from those in the naive group. Our study indicated low transmission risk of the virus in patients with SVF. Highlights: Generally the transmission risk from previously immunized patients, especially those with secondary vaccine failure (SVF), is lower than that from those with primary measles infections. We examined not only immunological but also virological differences between SVF (n = 22) and immunologically naive patients (n = 3) among an outbreak case at international airport in 2016. The number of viral genome copies in the blood specimens of those with SVF was significantly different and approximately 1/100 of that in immunologically naive patients. However, genome copy numbers in throat swabs and urine specimens were not significantly different between the groups. The virus was isolated only from those in the naive group. The virus was isolated only from those in the naive group.